The Implementation of Legal Measures Against Sexual Exploitation and Harassment in Kediri City - Handayani, Emi Puasa; Arifin, Zainal (Faculty of Law, Universitas Pekalongan, 2024)
AbstractionChild sexual exploitation and abuse represent grave violations of human rights with long-lasting consequences for victims. In Kediri City, these issues remain prevalent, raising significant concerns within the community. This paper seeks to analyze the legal enforcement measures addressing sexual exploitation and abuse in Kediri City. It explores several key aspects, including data and statistics concerning cases of sexual exploitation and abuse within the city, the law enforcement efforts undertaken by agencies such as the Kediri City Police, the Kediri City District Attorney's Office, and the Kediri City District Court. The paper also examines the challenges encountered in law enforcement, such as insufficient evidence, societal stigma against victims, and interference from particular parties. Furthermore, it discusses prevention initiatives undertaken by various stakeholders, including local government, civil society organizations, and the community. This study aims to enhance public understanding of sexual exploitation and abuse while advocating for more effective and victim-centred law enforcement practices.